Intact non-communicating rudimentary horn pregnancy in a patient with a history of two cesarean sections: A case report - Abdalla Ali Mohammed; Ahmed Ibrahim Abdelfattah; Mohammed Mahgoub Ali; Lodan Abdelrahman Elmubarak (Elsevier, 2024)
This article reports a case of an unruptured rudimentary horn viable pregnancy at 18 weeks of gestation. The diagnosis was missed at two previous cesarean sections and on a second-trimester ultrasound scan of the index pregnancy. The condition is extremely rare, life-threatening and difficult to diagnose. This case report highlights the importance of checking the anatomy of the uterus and appendages during cesarean section.